Brain mapping : the systems - Toga, Arthur W.; Mazziotta, John C. (Academic Press, 2000)
Brain mapping has forever altered and extended our understanding of the systems of the brain. The integrative capacity of brain maps enables the inclusion of a diverse array of observations and experimental results. Maps are used to describe brain structure, function, and connectivity, to catalog the ever-expanding knowledge base of human and animal nervous systems, to compare healthy tissue with diseased tissue, and to show detailed subsystems and circuits. Brain Mapping: The Systems is a compilation of the current research and developments in brain mapping. This book, the second in a series, provides an encyclopedic survey of brain maps characterizing the specific systems of the brain. It is a natural companion to Brain Mapping: The Methods because it describes the use of these techniques to create maps of the normal brain. It is an essential resource for all scientists, clinicians, and students interested in brain mapping. Key Features * Brings together the latest developments in brain mapping in one volume * Provides a detailed and chronological perspective of the field * Progresses from descriptions of underlying anatomic framework for mapping primary functional systems to more complex cognitive and emotional behaviors * Includes numerous full-color illustrations for comparing and contrasting brain structure and function * Allows for the integration of disparate information about the brain.